Manajemen Konflik dan Pola Komunikasi pada Kelompok Mahasiswa KKN - Renie Tri Herdiani; Robbi Kurnia Salim; Alfan Arfiansyah (Journal on Education, 2023)
In an environment or group there will inevitably arise differences of opinion or perceptions which if not quickly resolved will eventually become a prolonged conflict. Everyone should be able to overcome the problems he is experiencing so that they do not widen. We often hear the ability to handle conflict management. The purpose of this research is to find out conflict management and communication patterns in KKN student groups so that they can avoid problems that can arise during KKN. This research is a qualitative descriptive study with 3 students as respondents. Data collection methods used are observation, interviews and documentation. This study uses descriptive qualitative data analysis by analyzing data, reducing data, compiling data in units, categorizing data, determining data validity and interpreting data. The results of the study show that conflict management in the KKN group is in a good category because each member has the awareness to respect and respect one another, while the communication pattern used is an interpersonal communication pattern.